Analisis Keputusan Konsumen Membeli Ikan Segar Di Kota Waingapu Kabupaten Sumba Timur - Kumba, Yasinta Danga; Wadu, Junaedin (Universitas Galuh, 2024)
This study aims to analyze consumer decisions in buying fresh fish in Waingapu City, East Sumba Regency. The choice of Waingapu City as the research location was based on the consideration that the city is an economic center for the people of East Sumba Regency. In addition, Waingapu City was chosen because it has a large population of fresh fish sellers and consumers. Respondents used in this study amounted to 96 people who are fish buyers who are willing to be interviewed. The sampling technique in this study used a simple random sampling technique. To analyze the factors that influence consumer decisions in buying fish in Waingapu City, multiple linear regression analysis was carried out. The results of this study explain that location and price factors have a significant effect on consumers' decisions to buy fresh fish, while consumer tastes, product quality and consumer income have a significant influence on consumers' decisions to buy fresh fish. Simultaneously, location, price, consumer tastes, product quality, and consumer income have a significant effect on fresh fish purchasing decisions in Waingapu City.